Filsafat Eksistensialisme: Telaah Ajaran dan Relevansinya dengan Tujuan Pendidikan di Indonesia - Mahmudah Mahmudah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
existentialism is a school of modern philosophy that contains several very different branches, and has different influence. Commonly, philosophy discusses about God, macrocosms and microcosms, therefore existentialism centre its discussion about microcosms. In existentialism, there two school of thought, namely atheistic and theistic. From existentialism teaching, we cam understand that what individual and society produced are a step to enhancement. Therefore, there are sectors on human life that finished, from individual or society perspective. This has relevance with developing country like Indonesia that has been implement reformation at every side, include education.